2022
DOI: 10.3390/idr14030052
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Variants in Critically Ill Patients: A Comparison of the Delta and Omicron Variant Profiles

Abstract: Background: Coronavirus disease is a pandemic that has disrupted many human lives, threatening people’s physical and mental health. Each pandemic wave struck in different ways, infectiveness-wise and mortality-wise. This investigation focuses on critically ill patients affected by the last two variants, Delta and Omicron, and aims to analyse if any difference exists between the two groups. Methods: intensive care unit (ICU) COVID-19 consecutive admissions between 1 October 2021 and 31 March 2022 were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
0
28
1
Order By: Relevance
“…The SARS-CoV-2 pandemic has impacted every field of medicine, including intensive care, where each virus variant has differently affected critically ill patients [ 162 ]. The role of probiotics in infected patients in intensive wards has not been systematically explored.…”
Section: Harnessing the Microbiota In Critically Ill Patientsmentioning
confidence: 99%
“…The SARS-CoV-2 pandemic has impacted every field of medicine, including intensive care, where each virus variant has differently affected critically ill patients [ 162 ]. The role of probiotics in infected patients in intensive wards has not been systematically explored.…”
Section: Harnessing the Microbiota In Critically Ill Patientsmentioning
confidence: 99%
“…This discovery could, therefore, explain both the reduced incidence of pulmonary embolism associated with this variant [ 72 ] and the need to adapt prophylactic therapy with heparin, thus balancing both thrombotic and hemorrhagic risk. In a prospective study conducted on critically ill patients admitted because of COVID-19, Omicron patients had a lower incidence of pulmonary embolism than Delta ones [ 73 ]. Finally, Corriero et al reported that vaccines determine better protection in Omicron patients than Delta ones, and three vaccine doses increase protection in Omicron patients up to 60–75% [ 73 ].…”
Section: Different Variants Of Sars-cov-2 and Their Impact On Endothe...mentioning
confidence: 99%
“…In a prospective study conducted on critically ill patients admitted because of COVID-19, Omicron patients had a lower incidence of pulmonary embolism than Delta ones [ 73 ]. Finally, Corriero et al reported that vaccines determine better protection in Omicron patients than Delta ones, and three vaccine doses increase protection in Omicron patients up to 60–75% [ 73 ].…”
Section: Different Variants Of Sars-cov-2 and Their Impact On Endothe...mentioning
confidence: 99%
“…There is, in fact, only one publication analyzing the Delta–Omicron disparities concerning AKI in critically ill patients. Of note, the results have to be interpreted cautiously because of the small study group [ 69 ]. The comparison of 31 Omicron patients and 34 Delta patients revealed higher mortality rates and numbers of pre-existing comorbidities, as well as more frequent AKI incidence, in those who suffered from Omicron variant infection.…”
Section: Aki In the Omicron Eramentioning
confidence: 99%
“…The paradox of higher AKI prevalence in Omicron vs. Delta patients may result from faster virus replication for the price of less specialized cell tropism, priming the spreading of infection in the population over preference to specific organs [ 69 ]. Such low specialization with ubiquitous access would also add to the overall severe clinical status of Omicron patients in the ICU.…”
Section: Aki In the Omicron Eramentioning
confidence: 99%